2016
DOI: 10.1111/ped.13006
|View full text |Cite
|
Sign up to set email alerts
|

Polymyxin B‐immobilized fiber column direct hemoperfusion and continuous hemodiafiltration in premature neonates with systemic inflammatory response syndrome

Abstract: Active treatment with PMX-DHP and CHDF was helpful in the reduction of days on inhaled oxygen and tracheal intubation in preterm SIRS infants with hypercytokinemia. Further prospective randomized studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Although the characteristics and responses of neonatal sepsis differ from those of adults [5], PMX-HP reduced levels of immune mediators such as interleukin-6, highly mobile group-1 box protein, or interferon gamma in neonatal sepsis model [6], as in adult studies [3,7]. However, polymyxin Bimmobilized fiber cartridges for children as well as neonates are not available in most countries except Japan, and a few reports on its use in neonates have been found in the literature [8,9]. Here, we report a case of the successful application of adult polymyxin B-immobilized fiber column hemoperfusion to a neonate with carbapenem resistant Acinetobacter baumannii (CRAB) septic shock, who was on extracorporeal membrane oxygenation (ECMO) support.…”
mentioning
confidence: 99%
“…Although the characteristics and responses of neonatal sepsis differ from those of adults [5], PMX-HP reduced levels of immune mediators such as interleukin-6, highly mobile group-1 box protein, or interferon gamma in neonatal sepsis model [6], as in adult studies [3,7]. However, polymyxin Bimmobilized fiber cartridges for children as well as neonates are not available in most countries except Japan, and a few reports on its use in neonates have been found in the literature [8,9]. Here, we report a case of the successful application of adult polymyxin B-immobilized fiber column hemoperfusion to a neonate with carbapenem resistant Acinetobacter baumannii (CRAB) septic shock, who was on extracorporeal membrane oxygenation (ECMO) support.…”
mentioning
confidence: 99%
“…For example, in Japan, there are three sizes of PMX column: PMX-20R, PMX-05R, and PMX-01R, with blood volumes 135, 40, and 8 mL, respectively. The PMX-05R was used to treat sepsis in 10 children 9–48 months old ( 19 ), and PMX-01R was used in preterm infants ( 20 , 21 ). There were no reports of treatment complications.…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports of use of PMX-DHP being associated with improvement in pulmonary function, such as the P o 2 -to-F io 2 ratio in adults (9) and the arterial-to-alveolar P o 2 ratio in neonates (21). In this regard, use of PMX-DHP is associated with improvement in oxygenation in patients with sepsis and various lung diseases (22–25).…”
Section: Discussionmentioning
confidence: 99%
“…Endotoxin triggers a signaling cascade for leukocytes, macrophages, and endothelial cells to secrete various mediators including cytokines, leading to septic shock. Maeda et al [5] have shown that PMX-DHP treatment decreased the interleukin-6 level from ≥1,000 pg/mL to <500 pg/mL in 8 premature infants with systemic inflammatory response syndrome. Nishizaki and colleagues [1] reported in the letter to the editor that prognosis of septic neonates in earlier PMX-DHP induction was better than that in later PMX-DHP induction.…”
mentioning
confidence: 99%